The Physical and Biochemical Peculiarities of Representative Soils in Giurgeu Mountains - Lupașcu Angela; Chelariu Daniela (Present Environment and Sustainable Development, 2015)
The analyses for the description of physic-chemical and humus fractional characteristics have been determined for two soil subtypes, respectively four soil profiles, that are representative for the lower altitudes area of Giurgeu Mountains. The analysis has been based on: one Andi-Eutric Cambisols (EC an- 920 m alt.) and three Cambic Andosols (AN ca) situated at different altitudes: 1120-1140 m, 1197 m and 1310 m. The purpose of the research is to indentify some quantitative and qualitative differences in regards to some organic and inorganic components from the soil. Have come into prominence the sum of exchangeable bases, the total acidity exchange, the degree of base saturation and other aspects related to organic accumulation (the highest in Cambic Andosols: 1120-1140 m alt.), degree of humification (higher for the same Andosol and variable for the one from 1310 m alt.), the distribution curve on the profile of chemical and biochemical humic components. In terms of quality, there are differences in regard to the humification degree of organic matter, the dynamic on the profile of the main humus fractions (humic acids, fulvic acids, non-extractable material) forming the horizons of accumulation for some of the fractions.